PENGETAHUAN DAN PERILAKU TENTANG PEMELIHARAAN KESEHATAN GIGI MULUT - Bunda, Mutiara Permata; Wirakhmi, Ikit Netra; Triana, Noor Yunida (Jurnal Keperawatan dan Kesehatan, 2024)
Dental problems are a problem that is very prone to be obtained for children especially during their growth period. Oral health maintenance must be carried out early on at elementary school age considering that oral and dental diseases are ranked in the top ten most common diseases and are spread in various regions. Based on the phenomenon obtained at MI Ma'arif NU Karang Turi, there are 3 students who often experience oral health problems such as mouth ulcers, cavities and bleeding gums. Meanwhile, the other 2 students did not experience oral health problems which could result in disrupted activities and learning at school. The purpose of this study was to determine the level of knowledge and behavior about oral health maintenance in fifth grade students of MI Ma'arif NU Karang Turi. The instrument in this study was a knowledge and behavior level questionnaire. This research method uses quantitative research design. The sample in this study were 35 students. The sampling technique in this study used total sampling. The results of the description of the level of knowledge and behavior show that as many as 18 respondents with a percentage (51.4%) have a good level of knowledge. While as many as 19 with a percentage of respondents (54.3%) had poor behavior. Recommendations that can be given in this study are to make a consistent schedule or routine, for example after finishing dinner, then brush your teeth before bed.